Impact of the Syrian Crisis on the Competitiveness of Syrian Olive Oil in the International Markets - يعقوب غسان; عليو محمود; بدور غسان (Latakia University Journal -Biological Sciences Series, 2020)
This research aimed to study the evolution of the competitiveness indicators of Syrian exports of olive oil during the period of the Syrian crisis, in order to assess the new competitive position of these exports and identify the most important weaknesses or strengths. The research was based on quantitative and descriptive analysis methods. The main indicators were used to determine the competitive position, based on secondary data and time series related to Syrian olive oil trade indicators. The results showed that the exported quantities of Syrian olive oil decreased significantly from 43 thousand tons per year during the pre-crisis period to about 21 thousand tons per year during the crisis years, ie a decrease of -50.7%.This decline in the exported quantities was accompanied also by a high decline in the export prices of Syrian olive oil in the international market from 3.25 / kg during the pre-crisis period to 2.5 / kg, This means that it is about 33% lower than the world average price of about 3.7 / kg The total impact of the Syrian crisis on Syrian olive oil exports was estimated at a decrease of 22 thousand tons per year, due to the decline in the average market share of Syria’s olive oil exports from 2.8% of the total capacity of the global market during the pre-crisis period to only 1.1% during the crisis period. This is mainly due to the high competitive impact that contributed 132% of Syria’s share lost during the crisis period, which was estimated at 28.7 thousand tons. In addition, the geographical distribution of Syrian olive oil exports negatively affected the loss of a significant share of 2.3 thousand tons in the traditional imported markets, equivalent to 10.5% of its share lost during the crisis, which indicates the insufficient geographical distribution of Syrian olive oil export markets, which are concentrated in specific markets. In general, the export of olive oil in Syria during the crisis period was characterized by an apparent comparative advantage compared to the rest of Syria’s agricultural exports. The annual average for this indicator increased in the second period to about 19 per year compared to about 10, an increase almost doubled.